2004
DOI: 10.1158/1078-0432.ccr-03-0933
|View full text |Cite
|
Sign up to set email alerts
|

Id-1 and Id-2 Proteins as Molecular Markers for Human Prostate Cancer Progression

Abstract: Purpose: Id proteins are dominant-negative regulators of basic helix-loop-helix transcription factors that control malignant cell behavior in many different tissues. This study aimed to identify the potential role of Id-1 and Id-2 proteins as molecular makers for prostate cancer progression.Experimental Design: Using the technique of immunohistochemistry, we determined Id-1 and Id-2 expression in a panel of 67 human prostate biopsies. We also manipulated Id-1 and Id-2 expression in LNCaP and PC3 prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
105
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 27 publications
13
105
3
Order By: Relevance
“…Overexpression of Id-1 promotes mammary epithelial cell invasion (Desprez et al, 1998), and reduced expression of Id-1 in metastatic breast cancer cells leads to a decrease in invasiveness in vitro (Fong et al, 2003). Overexpression of Id-1 in prostate cancer cells also promotes metastasis through increased angiogenesis and invasiveness (Coppe et al, 2004). Reduced expressions of Id-1 and Id-3 have been demonstrated to inhibit the metastatic ability of gastric cancer cells (Tsuchiya et al, 2005), and Id-1 expression has been shown to be associated with the presence of invasion in endometrial carcinoma (Takai et al, 2001) and tumour angiogenesis in human pancreatic cancer (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Id-1 promotes mammary epithelial cell invasion (Desprez et al, 1998), and reduced expression of Id-1 in metastatic breast cancer cells leads to a decrease in invasiveness in vitro (Fong et al, 2003). Overexpression of Id-1 in prostate cancer cells also promotes metastasis through increased angiogenesis and invasiveness (Coppe et al, 2004). Reduced expressions of Id-1 and Id-3 have been demonstrated to inhibit the metastatic ability of gastric cancer cells (Tsuchiya et al, 2005), and Id-1 expression has been shown to be associated with the presence of invasion in endometrial carcinoma (Takai et al, 2001) and tumour angiogenesis in human pancreatic cancer (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that Id-2 promotes neoplastic transformation of oesophageal epithelial cells. Id-2 has been shown to bind and inhibit the function of retinoblastoma protein, a tumour suppressor protein (Iavarone et al, 1994;Lasorella et al, 1996) and therefore has been implicated in tumour progression in several cancer types (Maruyama et al, 1999;Fukuma et al, 2003;Coppe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Using a commercially available antibody, elevated Id1 protein expression levels have been reported in diverse human cancers, including epithelial malignancies of ovary, colon, pancreas, nasopharynx, stomach, and esophagus; in neural tumors; melanomas; Ewing's sarcoma; seminoma; leukemia; and, more recently, bladder transitional cell carcinoma (1,5). Previous studies in prostate cancer found intense immunoreactivity in some tumor cells and related this to a poorer prognosis (4,6). Similarly, studies in mammary cancers found that a majority of the tumors showed some level of Id1 protein expression (3).…”
Section: Discussionmentioning
confidence: 99%
“…The expression and role of the Id1 protein in epithelial cancer cells, however, is controversial. For example, some investigators have reported that the neoplastic cells of breast, prostate, and bladder carcinomas express the Id1 protein, and that this finding correlates in some cases with poor prognosis (3)(4)(5)(6). Others, however, have reported Id1 protein expression in mammary tumors only in the endothelial cells of blood vessels associated with these lesions (7).…”
Section: Introductionmentioning
confidence: 99%
“…Increased Id-1 expression was detected during carcinogenesis of the prostate in the Noble rat (Ouyang et al, 2001). In human specimens, Id-1 expression in prostate cancer is increased in comparison to benign prostatic hyperplasia specimens (Ouyang et al, 2002a), and increased expression of Id-1 is correlated with Gleason score, reflecting the aggressive nature of Id-1-positive prostate cancers (Ouyang et al, 2002a;Coppe et al, 2004;Yuen et al, 2006). This information suggests that Id-1 is important in both prostate cancer initiation and progression.…”
mentioning
confidence: 85%